Use of a Non-parametric Bayesian Method to Model Health State Preferences: An Application to Polish and Irish EQ-5D-5L Valuations - Kharroubi, Samer A.; Kelleher, Dan (Frontiers in Public Health, 2022)
Valuations of preference-based measures for health are conducted in different countries. There is scope to use results from existing countries’ valuations to generate better valuation estimates than analysing the data from each country separately. We analyse data from two smaller design EQ-5D-5L valuation studies where a sample of 119 Polish migrants and 123 native Irish valued 30 common health states using similar composite time trade-off protocols. We apply a nonparametric Bayesian method to provide better predictions of the Polish (Irish) population utility function when the existing Irish (Polish) results were used as informative priors. The resultant new estimates were then compared to those obtained by analysing the data from each country by itself via different prediction criterions. The results suggest that existing countries’ valuations could be used as potential informative priors to produce better valuation estimates under all prediction criterions used. The implications of these results will be hugely important in countries where valuation studies are expensive and hard to conduct. Future application to other countries and to other preference-based health measures are encouraged.